Assessment of a New England Public University's Adherence to the Partnership for a Healthier America's Healthier Campus Initiative. (14th June 2022) - Cherry, Maria; Vadiveloo, Maya; Parker, Haley
Abstract: Objectives: University dining halls are understudied food environments that affect the diet quality of college students. This study assessed dining hall offerings at a large public university using the Partnership for a Healthier America's Healthier Campus Initiative (PAHA), criteria for healthier campus food environments. Methods: We evaluated breakfast, lunch, and dinner using spring cycle menus (16 weeks in 2019 and 4 in 2021) from two full-service dining halls totaling 29 meals in 2019, and 84 meals in 2021 to determine adherence with PAHA criteria for availability of: 1) wellness meals (defined as including whole grains, lean protein, low-fat dairy, fruits and vegetables), 2) ³5 fruits, ³5 vegetables, and ³2 100% whole grain products, 3) ≤4 fried food options at a time, 4) ³3 desserts with <150 kcals, labelled as healthier 5) healthier food identification at point of presentation, and 6) marketing strategies promoting healthy options. To assess validity of the cycle menu data, evaluators also completed 7 in-person visits to match the cycle menus to the dining hall's physical displays. An "all-day" menu (ADM) was also collected from both years to evaluate static items available. Results: All spring 2019 and spring 2021 cycle menus consistently met PAHA criteria for fried foods, but 0% of cycle menus during either period met the other 5 criteria. In 2019, wellness meals and fruits, vegetable, and whole grain criteria were met when the ADM was included in the analysis; in 2021, the wellness meals was met when salad and sandwich bars offerings in the ADM were included. Cycle menus were consistent with what evaluators observed in-person. Even with the ADM, dining hall menus did not meet criteria for desserts or marketing of healthier options. Conclusions: Compared against guidance for healthy campus food environments, dining halls at a large public university largely met limited fried food criteria but did not meet other criteria. While increasing whole grains, fruits, vegetables, lean meat, and low-fat dairy in cycle menus may have budgetary and/or logistical constraints, it may be feasible for dining halls to clearly label and promote healthier foods at point-of-purchase through signage. Funding Sources: URI College of Health Sciences Undergraduate Research Award, April 2021.